A construção da governança ambiental nos municípios brasileiros: o caso de Colinas do Tocantins (TO) - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
This paper aims to analyze the construction of environmental governance in Brazilian cities, characterized as the ability of governments to plan, formulate and implement policies in collaboration with civil society, particularly in the implementation of legislative and regulatory environment, culminating in the creation and strengthening of public and private organizations focused on environmental protection.The depletion of natural resources requires a new attitude of citizens, for the continuity of life on the planet. Within this reality and with the aim of searching aspects of environmental governance, especially in the municipal government of Colinas do Tocantins, was conducted a survey of municipal environmental legislation as well as analysis of secondary data obtained from the local Environmental research 2002, public bodies As the Municipal Department of Environment and before social bodies.. The social participation in the city of Colinas do Tocantins is fragile, because there is more environmental problems. The study found a city with considerable degree of progress in the provision of instruments for environmental management in the period between the years 2002-2008, however the lack of relevance for environmental issues, makes the city stage classics of environmental problems as inadequate disposal of waste solid, water contamination, among others. The municipal competencies and social performance are key pieces in achieving the goals pursued by the law to protect the environment and that is what will show how important is the need for a harmonious relationship between the householders, the public and the environment. This requires that civil society can participate effectively in decision-making, either through the formulation of public policies is for implementation, I mean, we must implement mechanisms for participation, ensuring the exercise of environmental citizenship. Making effective civil society participation can occur differently and this study examines the form of actions of civil society organizations in the environmental policy of the City of Colinas do Tocantins. To do so is made a diagnosis of the composition and role of eating and Civil Society organizations, emphasizing that although embryonic, the second segment that participation is central to the formulation and implementation of public policies and environmental well for the preservation and conservation of social and biodiversity. Analysis of these data possible to build the profile of environmental management implemented in the municipality, and verification of the fragility of governance. From this perspective, we investigated the environmental management practiced and characterized as unfit for the protection of the natural environment and quality of life
Keywords: Competências do Município; Colinas do Tocantins; Governança Ambiental; Participação; Skills of the County, Colinas do Tocantins, Environmental Governance, Participation; CIÊNCIAS AGRÁRIAS